Utilization of Nypa (Nypa fruticans) Bark for Making Biocharcoal Briquette as Alternative of Energy Sources - Mulyadi, Arie Febrianto; Dewi, Ika Atsari; Deoranto, Panji (Jurnal Teknologi Pertanian, 2013)
This research aim are to get combination of the best treatment between the amount of tapioca glue and lime as additional material to be able to produce charcoal briquette which is able to be taken the beneficial as alternative energy source, and to know production price which needed in making leaf sugarcane biocharcoal briquette. The experiment for this research is Completely Randomized Block Design with 2 factors;, they are concentration of Tapioca glue (P) and Concentration of lime as additional material (K). Each of the factors has three levels, they are: P1 (20 %), P2 (30 %), and P3 (40 %); K1 (1%), K2 (3%), K3 (5%) which are repeated twice. Product yield, water content, endurance press, heat value, and ash content are analysed on this reserach. The best treatment is on biocharcoal briquette with the tapioca glue is 20% and lime is 5% with product yield is 78.04%, water content is 4.10%, the endurance press is 157.57 kg/cm2, heat value is 2753.71 cal/g, and ash content is 22.35%. The result of production analysis show the base price of the product is Rp. 1120.00/ kilogram. The price of product sold is Rp. 1700/ kilogram with profit expectation is 40 so that the BEP value (unit) is 11986.03 kilograms or Rp.18224978.07. Keywords: biocharcoal, briquette, lime, nypa bark, tapioca.